A Review on the Dietary Flavonoid Tiliroside. Issue 5 (17th August 2018) - Grochowski, Daniel M.; Locatelli, Marcello; Granica, Sebastian; Cacciagrano, Francesco; Tomczyk, Michał
Abstract: Among flavonoid derivatives, tiliroside is a flavonoid contained in several edible plants or specific plant parts (fruits, leaves, or roots). These parts are often widely used as both food and medicines, in the treatment of various ailments and, in some cases, as food supplements. Considering the easy access to many publications concerning tiliroside and the lack of a review that summarizes the current progress in studies on its safety, efficacy, and presence in the plant kingdom, we present here a review paper on tiliroside and its principal derivatives. The paper also highlights the basic knowledge regarding this molecule, its derivatives, and the analytical approaches used for extraction and quantification, as well as reports on the biological activities against different key enzymes linked to various human diseases. The reported information is also devoted to highlighting the concept "learn from nature to discover new products, " particularly in the development of new drugs, food supplements, and nutraceuticals, starting from a natural lead compound such as tiliroside and improving its biological activities (and selectivities) against a specific target for therapeutic purposes.